2018
DOI: 10.1136/bjsports-2017-098937
|View full text |Cite
|
Sign up to set email alerts
|

The Adductor Strengthening Programme prevents groin problems among male football players: a cluster-randomised controlled trial

Abstract: ISRCTN98514933.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
6
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 37 publications
8
145
6
4
Order By: Relevance
“…Despite these results, suggesting that reach of the program was successful, the players reported to deviate from the recommended protocol. In the present study, about 45% of the players reported to have performed the program at least as often as prescribed, while data from the RCT documented an average weekly completion of the program of 70% . However, the discrepancy may not be contradictory.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Despite these results, suggesting that reach of the program was successful, the players reported to deviate from the recommended protocol. In the present study, about 45% of the players reported to have performed the program at least as often as prescribed, while data from the RCT documented an average weekly completion of the program of 70% . However, the discrepancy may not be contradictory.…”
Section: Discussioncontrasting
confidence: 57%
“…The groin‐specific interventions have had a combined focus on hip adductors, flexors, and abdominals . However, recently, the Adductor Strengthening Programme, a simple, single‐exercise program based on the Copenhagen Adduction exercise, was shown to reduce the risk of groin problems among male football players with 41% …”
Section: Introductioncontrasting
confidence: 57%
See 3 more Smart Citations